Исследования Волчанского городища - Колода, В.В. (My University, 2004)
V. Koloda New researches of Volchansk's settlement This article is about the researches of the Early Middle Ages defensive fortifications in the Volchansk site of settlement in Kharkov region, which is dated to mid VIII century -mid X century A.D. and relates to the Saltov archeological culture. This work tells us about the dynamics and the technology of building of these defenses. It traces the similarity of the building technology of the Volchansk site of settlement and the building technology of people in Kuban region in the Middle Ages.